Hb A2 Episkopi – a novel δ-globin chain variant [HBD:c.428C>T] in a family of mixed Cypriot–Lebanese descent. Issue 5 (28th May 2017) - Lederer, Carsten W.; Pavlou, Eleni; Tanteles, George A.; Evangelidou, Paola; Sismani, Carolina; Kolnagou, Annita; Sitarou, Maria; Christou, Soteroulla; Hadjigavriel, Michael; Kleanthous, Marina
ABSTRACT: Objectives: Thalassaemia is a potentially lethal inherited anaemia, caused by reduced or absent synthesis of globin chains. Measurement of the minor adult haemoglobin Hb A2, combining α- with δ-globin, is critical for the routine diagnosis of carrier status for α- or β-thalassaemia. Here, we aim to characterize a novel δ-globin variant, Hb A2 Episkopi, in a single family of mixed Lebanese and Cypriot ancestry with mild hypochromic anaemia and otherwise normal globin genotype, which also presents with a coincidental 0.78-Mb sequence duplication on chromosome 1 (1q44) and developmental abnormalities. Methods : Analyses included comprehensive haematological analyses, cation-exchange high-performance liquid chromatography (CE-HPLC), cellulose acetate electrophoresis (CAE), Sanger sequencing and structure-based stability predictions for Hb A2 Episkopi. Results : The GCT > GTT missense mutation, underlying Hb A2 Episkopi, HBD:c.428C > T, introduces a cd142 codon change in the mature protein, resulting in reduced normal Hb A2 amounts and a novel, less abundant Hb A2 variant (HGVS: HBD:p.A143V), detectable as a delayed peak by CE-HPLC. The latter was in line with structure-based stability predictions, which indicated that the substitution of a marginal, non-helical and non-interface residue, five amino acids from the δ-globin chain carboxy-terminus, was moderately destabilizing. Discussion : Detection of the new variant depends on the diagnostic set-up and had failed by CAE and on an independent CE-HPLC system, which, in unfavourable circumstances, may lead to misdiagnoses of β-thalassaemia as α-thalassaemia. Given the mixed background of the affected family, the ethnic origin of the mutation is unclear, and this study thus suggests awareness for possible detection of Hb A2 Episkopi in both the Cypriot and the Lebanese populations.